Utilization of Banana Peel Waste as Anti-bacterial Organic Gloves with Latex Addition - Sari*, Sri Adelila; Kabeakan, Feri Yuni; Purba, Elsa Christine; Vedha, Renjana Sekar; Simarmata, Yesi Angelia; Aldi, Irfan; Hasibuan, Hanisah (Jurnal IPA & Pembelajaran IPA, 2024)
The increased use of synthetic gloves made from plastics such as nitrile and vinyl resulted in serious environmental problems due to plastic waste that was difficult to decompose. This study aimed to utilize banana peel waste for producing antibacterial organic gloves with the addition of latex. The manufacturing method involved mixing latex with ionol as an antioxidant, sulfur for vulcanization, and banana peel powder to add antibacterial properties. Tensile strength testing was conducted by varying the proportion of banana peel and chemical treatment using NaOH and NH4OH solutions. The results showed that increasing the proportion of banana peel led to a decrease in tensile strength and elongation of the material, from 22.5 MPa and 550% at a 10% banana peel ratio to 16.0 MPa and 480% at a 40% ratio. Treatment with NaOH resulted in a greater reduction than NH4OH. This study demonstrated that banana peels had potential as an environmentally friendly additive for the manufacture of antibacterial organic gloves. To improve its effectiveness, it was recommended that future research focus on optimizing the proportion of ingredients, developing the production process, and evaluating costs to achieve an optimal balance between quality, durability, and production efficiency